A purpose of a copy of 16,500 gr. and another that originated Placenta accreta - Palma Guevara, Roberto (2015)
Two cases of uterine fibromatosis among others, found in gynecological practice in the Hsopital "Nuestra Señora del Rosario" Cajabamba, product treatment in patients who arrive when their complaints are severe are specifically disclosed. These two tumors are particularly important: one for his significant weight (16,500 g.) And a uterus that originated multifibromatoso placenta accreta that contempt and empirical attention killed the patient. Brief description of the recent literature concludes that it is the most common pathology among tumors and orogona 15% of gynecological conditions.